PENERAPAN METODE TOPSIS DALAM EVALUASI KINERJA PADA PT. BPR PANDANARAN JAYA - Karlena Indriani; Anastasia Siwi Fatma Utami; Ali Haidir; Ahmad Sinnun; Yopi Handrianto; Ade Christian; Hariyanto Hariyanto (Program Studi Sistem Informasi, Universitas Banten Jaya, 2023)
This study was done at PT BPR Pandanaran Jaya so that the TOPSIS (Technique for Order of Preference by Similarity to Ideal Solution) method could be used to improve how employee work is judged. Employee performance is an important part of a company's growth, and employee performance evaluations are done to find high-performing workers and help them improve. In this study, it was found that PT BPR Pandanaran Jaya has hardworking workers who are very committed to doing their jobs well. But there are also workers who need to work on how well they do their jobs. The TOPSIS method is used to compare how well each employee does their job based on important factors. The data showed that Linda Luciana Anggraeni and Dwi Jasminto were the employees with the best performance ratings, followed by Rudi Purnama. Mita Safira Mediana, Mia Arifah, Gea Ananda, Indra Utama, and Yunia Ningrum, on the other hand, were given lower scores for their work. Overall, PT BPR Pandanaran Jaya has high-performing workers, but some of them could do better. So, the company can use the results of this review to come up with plans to help employees grow, give them more training, and give them the help they need to improve their total performance. With these steps, PT BPR Pandanaran Jaya should be able to reach its organizational goals and keep a skilled and productive work team.